Integrated Network Pharmacology Analysis and Pharmacological Evaluation to Explore the Active Components and Mechanism of Abelmoschus manihot (L.) Medik. on Renal Fibrosis - Gu L; Hong F; Fan K; Zhao L; Zhang C; Yu B; Chai C (Dove Medical Press, 2020)
Lifei Gu,1 Fang Hong,1 Kaikai Fan,1 Lei Zhao,1 Chunlei Zhang,1 Boyang Yu,1,2 Chengzhi Chai1 1Jiangsu Key Laboratory of TCM Evaluation and Translational Research, School of Traditional Chinese Pharmacy, China Pharmaceutical University, Nanjing 211198, People’s Republic of China; 2Research Center for Traceability and Standardization of TCMs, School of Traditional Chinese Pharmacy, China Pharmaceutical University, Nanjing 211198, People’s Republic of ChinaCorrespondence: Chengzhi Chai; Boyang YuJiangsu Provincial Key Laboratory for TCM Evaluation and Translational Development, China Pharmaceutical University, Nanjing, Jiangsu 211198, People’s Republic of ChinaTel +86 25 86185955Fax +86 2586185158Email chengzhichai@cpu.edu.cn; boyangyu59@163.comBackground: Renal fibrosis is a common pathological outcome of chronic kidney diseases (CKD) that is considered as a global public health issue with high morbidity and mortality. The dry corolla of Abelmoschus manihot (L.) Medik. (AMC) has been used for chronic nephritis in clinic and showed a superior effect in alleviating proteinuria in CKD patients to losartan. However, the effective components and underlying mechanism of AMC in the treatment of renal fibrosis have not been systematically clarified.Methods: Based on drug-likeness evaluation, oral bioavailability prediction and compound contents, a systematic network pharmacology analysis was conducted to predict the active ingredients. Gene Ontology, Kyoto Encyclopedia of Genes and Genomes pathway analysis and protein–protein interaction analysis were applied to predict the potential pathway and target of AMC against renal fibrosis. The formula of component contribution index (CI) based on the algorithm was used to screen the principal active compounds of AMC in the treatment of renal fibrosis. Finally, pharmacological evaluation was conducted to validate the protective effect and primary predicted mechanism of AMC in the treatment of renal fibrosis on a 5/6 nephrectomy mice model.Results: Fourteen potential active components of AMC possessing favorable pharmacokinetic profiles and biological activities were selected and hit by 17 targets closely related to renal fibrosis. Quercetin, caffeic acid, 9.12-octadecadienoic acid, and myricetin are recognized as the more highly predictive components as their cumulative contribution rate reached 85.86%. The AMC administration on 5/6 nephrectomy mice showed a protective effect on kidney function and renal fibrosis. The hub genes analysis revealed that AMC plays a major role in inhibiting epithelial-to-mesenchymal transition during renal fibrosis.Conclusion: Our results predicted active components and potential targets of AMC for the application to renal fibrosis from a holistic perspective, as well as provided valuable direction for further research of AMC and improved comprehension of renal fibrosis pathogenesis.Keywords: Abelmoschus manihot (L.) Medik., network pharmacology, renal fibrosis, 5/6 nephrectomy, active components